Chemical Proteomics-Guided Identification of a Novel Biological Target of the Bioactive Neolignan Magnolol - Cassiano, Chiara; Esposito, Roberta; Tosco, Alessandra; Casapullo, Agostino; Mozzicafreddo, Matteo; Tringali, Corrado; Riccio, Raffaele; Monti, Maria Chiara (Frontiers in Chemistry, 2019)
Understanding of the recognition process between bioactive natural products and their specific cellular receptors is of key importance in the drug discovery process. In this outline, some potential targets of Magnolol, a natural bioactive compound, have been identified by proteomic approaches. Among them, Importin-β1 has been considered as the most relevant one. A direct binding between Magnolol and the nuclear chaperone has been confirmed by DARST and molecular docking, while its influence on Importin-β1translocation has been evaluated by in vitro assays.